RESEARCH OF THE CHANGE OF THE STABILIZER CONSTRUCTION MODEL WITH THE PURPOSE OF INCREASING ACCURACY - BEZVESILNA, OLENA; NECHAI, SERGEY; TOLOCHKO, TETIANA; GRYNEVYCH, MARIIA (Herald of Khmelnytskyi National University. Technical sciences, 2023)
The article solves an actual problem - changes in the stabilizer construction model are investigated in order to increase accuracy. In the process of optimization, the main variants of the optimal values of the adjustment coefficients of the stabilizer control unit were determined. For the first three variants of the tuning coefficients, comparative modeling was carried out using two types of DCS: GT 46 and G20-075-100 with a bandwidth of 100 Hz. It is shown that an increase in the amplification factor has a positive effect on the rigidity of the system. It is shown that, in contrast to the stabilizer using GT46, the introduction of the DCS MEMS allows to increase the amplification factor and thereby increase the rigidity of the system. As a result of the simulation, it is shown that the acceptable dynamic error is preserved when the amplification factor is further increased to Ku = 109 and Ku = 116. An increase in the Ku coefficient to a value of 122 leads to an increase in the fluctuation of the dynamic error of the stabilizer. It was established that with a decrease in the amplification factor, the nature of the change in the amplitude of the dynamic error for the GT-46 and G20-075-100 DCS coincides. It was established that the high-frequency oscillations that occur are caused by a rather high amplification factor Ku=102. It is shown that the use of the DCS MEMS, which is characterized by high resonant frequencies, makes it possible to exclude the bandpass filter from the stabilizer. It was established that with an increase in the bandwidth of the DCS, a smoother working out of the given harmonic influence is ensured. It was determined that an increase in accuracy characteristics can be achieved by reducing the discreteness of processing by the digital computer of the control unit to 1.0 ms and a bandwidth of at least 100 Hz. High requirements for the accuracy of the stabilizer are ensured - the dynamic error does not exceed 1 td. (3.6 angular min).
Keywords: stabilizer; dynamic error; modeling; harmonic influence; impulse influence; adjustment factors; gain factor